IT success! : towards a new model for information technology - Gentle, Michael, 1957- (John Wiley & Sons, 2007)
"Fifty years after the birth of corporate computing, IT today is still characterized by 50-70% project failure rates. Which is pretty scary when you come to think of it: either a goblin has cast a spell on a whole profession - or that profe